Influence of Customer Trust and Price Perception on Customer Satisfaction at PT Arindo Jaya Mandiri Semarang - Arum Suprapti; Kurniani (Politeknik Negeri Semarang, 2025)
This study aims to analyze the influence of customer trust and price perception on customer satisfaction at PT Arindo Jaya Mandiri Semarang. This study used a quantitative approach with a saturated sampling method, where all the company's customers during the 2023–2024 period were sampled. Data processing was performed using SPSS version 20, with analysis techniques including validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination, F-test, and t-test. The results showed an Adjusted R Square value of 0.541, indicating that customer trust and price perception simultaneously influence customer satisfaction by 54.1%. The remaining 45.9% is influenced by other variables not examined, such as service speed, communication, and external market conditions